STEP TOWARDS IN-SITU ELECTROKINETIC REMEDIATION OF CONTAMINATED SOILS IN PAKISTAN - Khalid, Maria; Qureshi, R. M.; Ahmed, N. (The Nucleus, 2020)
Electrokinetic remediation (EKR) technology has fast emerged as a reliable, powerful and highly prominent candidate for effective in situ removal of soluble and leachable toxic species of metals, radionuclides, organics from contaminated soil and water environment. Many developing countries are now employing this technology with great success for on-site decontamination of waste soils. Nevertheless, in Pakistan, such a technology has never been developed for in-situ remediation of toxic species in waste soils. This paper presents a brief account of our initial efforts made at PINSTECH, Islamabad regarding development and operation of electrokinetic cell for lab-scale remediation of toxic metals (also organic pollutants and radio-metals) and EKR related specific analysis of soil samples collected from three target sites (Korangi Industrial Zone-Karachi, Kala Shah Kaku-G.T. Road, and near Village Nilore, Islamabad).